Zwitterionic‐Coated "Stealth" Nanoparticles for Biomedical Applications: Recent Advances in Countering Biomolecular Corona Formation and Uptake by the Mononuclear Phagocyte System. Issue 13 (31st March 2014) - García, Karina Pombo; Zarschler, Kristof; Barbaro, Lisa; Barreto, José A.; O'Malley, William; Spiccia, Leone; Stephan, Holger; Graham, Bim
<x xml:space="preserve">Abstract</x> Nanoparticles represent highly promising platforms for the development of imaging and therapeutic agents, including those that can either be detected via more than one imaging technique (multi‐modal imaging agents) or used for both diagnosis and therapy (theranostics). A major obstacle to their medical application and translation to the clinic, however, is the fact that many accumulate in the liver and spleen as a result of opsonization and scavenging by the mononuclear phagocyte system. This focused review summarizes recent efforts to develop zwitterionic‐coatings to counter this issue and render nanoparticles more biocompatible. Such coatings have been found to greatly reduce the rate and/or extent of non‐specific adsorption of proteins and lipids to the nanoparticle surface, thereby inhibiting production of the "biomolecular corona" that is proposed to be a universal feature of nanoparticles within a biological environment. Additionally, in vivo studies have demonstrated that larger‐sized nanoparticles with a zwitterionic coating have extended circulatory lifetimes, while those with hydrodynamic diameters of ≤5 nm exhibit small‐molecule‐like pharmacokinetics, remaining sufficiently small to pass through the fenestrae and slit pores during glomerular filtration within the kidneys, and enabling efficient excretion via the urine. The larger particles represent ideal candidates for use as blood pool imaging agents, whilst the small ones provide a highly promising platform for the future development of theranostics with reduced side effect profiles and superior dose delivery and image contrast capabilities.